Improving grain quality in winter wheat (Triticum aestivum L.) by introgressing alien HMV glutenin genes from tetraploid Triticum and diploid Aegilops species:.. - Pilch, Józef (Plant Breeding and Seed Science, 2007)
Significant progress has recently been made in elucidating the genetics of high molecular weight (HMW) glutenins and how they affect bread-making quality. There are hundreds of genotypes of T. aestivum with different combinations of alleles at loci Glu-A1, Glu-B1 and Glu-D. The combination of alleles has a major effect on bread-making quality. Improving grain quality in T. aestivum is difficult with conventional methods...